Early national trends in non-abortion reproductive care access after Roe - Zhao, Junying; Zahn, Aaron; Pang, Samuel C.; Quang, Tony S.; Campbell, Janis; Halkitis, Perry N. (Frontiers in Public Health, 2024)
Background Roe was overturned in 2022. No peer-reviewed evidence exists for the indirect spillover effects of overturning Roe on non-abortion reproductive care access for diverse patient populations. Methods National data were from 2013–2023 HHS Title X Directory, 2013–2020 CDC Artificial Reproductive Technologies (ART) Surveillance and 2021–2023 manual collection, and Guttmacher Institute. Outcome measures included numbers of ART clinics and Title X entities. Title X entities are those that receive federal funds to establish and operate voluntary family planning projects, especially for low-income patients. We reported pre-and post-Roe changes, associations between changes in measures and abortions, and characteristics of changed measures by region and political geography. Results Post-Roe America witnessed national declines of 1.03% in ART clinics and 18.34% in Title X entities, and average state decreases of 0.08 ART clinics (p < 0.05) and 18 Title X entities (p < 0.001). State-level ART clinic closures and abortion reductions had little association except for Texas, Oklahoma, Arizona, New York, and California. Plummets in Title X entities and abortions were positively associated: Reducing 100 abortions was associated with defunding two Title X entities (p < 0.05). The South experienced the largest losses of both, while 83.39% of lost Title X entities were in states that voted Republican in the 2020 presidential election, disproportionate to the 49.02% of states that voted Republican and the 42.52% of US population residing in these states. Conclusion We provide one of the first few evidence of spillover impacts of overturning Roe on non-abortion care access for diverse populations: low-income men and women, single parents by choice, and biologically and socially infertile patients. Early evidence warns of worsening challenges of inequities and calls for immediate policy actions.